Sliding mode controller for robust force control o hydraulic actuator with environmental uncertainties - Boumhidi, Jaouad; Mrabti, Mostafa (Revista Colombiana de Computación, 2005)
In this paper, a reduced order linear model is selected to describe the hydraulic servo-actuator with large environmental uncertainties. The exploitation in simulation of the perturbed 5th order linear model is enough for the first approach, that is to say, before experimentation to value the studied law control potential. Because its robust character and superior performance in environmental uncertainties, a sliding mode controller, based on the so called equivalent control and robust control components is designed for control of the output force to track asymptotically the desired trajectory with no chattering problems. A comparison with H-infinity controller shows that the proposed sliding mode controller is robustly performant. Keywords : Sliding mode control, hydraulic Servo-Actuator, output tracking.